[tex]\boxed{\text{SA} = 2(\text{L} \text{W}) + 2(\text{L} \text{H}) + 2(\text{B} \text{H})}[/tex]

Step-by-step explanation:

We know that the surface area is the sum of the area of the prism's faces.

It should be noted that the area of any face is equal to the area of its opposite face. Thus, we get the following equation for the surface area:

[tex]\implies\text{SA = 2(} \text{Area of rectangle}_{1} ) \ + \ \text{2}(\text{Area of rectangle}_{2} ) \ + \ \text{2}(\text{Area of rectangle}_{3} )[/tex]

A model has been drawn of the rectangular prism. (image)

Let the dimensions (length, width, and height) of the prism be known as L, B, and H respectively. Then, we get the following:

[tex]\implies \text{SA} = 2(\text{L} \times \text{W}) + 2(\text{L} \times \text{H}) + 2(\text{B} \times \text{H})[/tex]

[tex]\implies \boxed{\text{SA} = 2(\text{L} \text{W}) + 2(\text{L} \text{H}) + 2(\text{B} \text{H})}[/tex]

Learn more about surface area: